Design of Private Geographycal Information System (GIS) Server for Battlefield Management System - Alde Alanda; Erwadi Bakar (Politeknik Negeri Padang, 2017)
Geographic Information System (GIS) data is needed for model earth surface in 3D simulation for SAR operation to make simulation process as real as possible. Adding integrated GIS data server to simulation system make simulation application user does not need to input and prepare the GIS data manually, by reducing simulation application user task, user can more concentrate on simulation process.In this research the design and implementation of GIS data application that can provide the data needed by a simulation application using existing data on the online map provider. Application designed to display data necessary to carry out the conversion of GIS data to the format used in the simulation . Based on the test resuls of the conversion of GIS data to map format generated simulation has the same texture to the original map. Simulations can be run by using the map conversion and the simulation can run using real map but the level of height accuracy is not optimal.